logo

Ask Questions, Get Answers

 
X
 Search
Want to ask us a question? Click here
Browse Questions
Ad
Home  >>  CBSE XI  >>  Math  >>  Limits and Derivatives
0 votes

Find the derivative of $(5x^3+3x-1)(x-1)$

Can you answer this question?
 
 

1 Answer

0 votes
Let $f(x) = (5x^3+3x-1)(x-1)$
By Leibnitz product rule,
$ f'(x) = (5x^3+3x-1) \large\frac{d}{dx}$$(x-1)+(x-1) \large\frac{d}{dx}$$(5x^3+3x-1) $
$ = (5x^3+3x-1) (1) +(x-1)(5.3x^2+3-0)$
$ = (5x^3+3x-1) +(x-1)(15x^2+3)$
$ = 5x^3+3x-1+15x^3+3x-15x^2-3$
$ = 20x^3-15x^2+6x-4$
answered Apr 9, 2014 by thanvigandhi_1
 

Related questions

Ask Question
student study plans
x
JEE MAIN, CBSE, NEET Mobile and Tablet App
The ultimate mobile app to help you crack your examinations
Get the Android App
...